The Role of Mucosal Immunity in Pertussis - Solans, Luis; Locht, Camille (Frontiers in Immunology, 2019)
Pertussis or whooping cough, mainly caused by Bordetella pertussis, is a severe respiratory disease that can affect all age groups but is most severe and can be life-threatening in young children. Vaccines against this disease are widely available since the 1950s. Despite high global vaccination coverage, the disease is not under control in any country and its incidence is even increasing in several parts of the world. Epidemiological and experimental evidence has shown that the vaccines fail to prevent B. pertussis infection and transmission, although they are very effective in preventing disease. Given the high infection rate of B. pertussis, effective control of the disease likely requires prevention of infection and transmission in addition to protection against disease. With rare exceptions B. pertussis infections are restricted to the airways and do usually not disseminate beyond the respiratory epithelium. Therefore, protection at level of the respiratory mucosa may be helpful for an improved control of pertussis. Yet, compared to systemic responses, mucosal immune responses have attracted relatively little attention in the context of pertussis vaccine development. In this review we summarize the available literature on the role of mucosal immunity in the prevention of B. pertussis infection. In contrast to vaccination, natural infection in humans and experimental infections in animals induce strong secretory IgA responses in the naso-pharynx and in the lungs. Several studies have shown that secretory IgA may be instrumental in the control of B. pertussis infection. Furthermore, studies in mouse models have revealed that B. pertussis infection, but not pertussis vaccination induces resident memory T cells, which may also contribute to protection against colonization by B. pertussis. As these resident memory T cells are long lived, vaccines that are able to induce them should provide long-lasting immunity. As of today, only one vaccine designed to induce potent mucosal immunity is in clinical development. This vaccine is a live attenuated B. pertussis strain delivered nasally in order to mimic the natural route of infection. Due to its ability to induce mucosal immunity it is expected that this approach will contribute to improved control of pertussis.